2011
DOI: 10.1021/jp208510d
|View full text |Cite
|
Sign up to set email alerts
|

Computational Insight into the Carbenic Character of Nitrilimines from a Reactivity Perspective

Abstract: Nitrilimines (R-CNN-R) can be described through a carbenic valence bond structure, and although intermolecular carbenic reactions from nitrilimines are unknown, intramolecular reaction products from ortho-vinyl MeCOO-CNN-Ph (1) and Ph-CNN-Ph (2) that seem to have followed two typical carbene reaction mechanisms, [1+2] cycloaddition and C-H insertion, have been reported. This study sheds light on whether such reaction mechanisms are tenable, using the electron density and its Laplacian (QTAIM), natural bond orb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 57 publications
(125 reference statements)
1
14
0
Order By: Relevance
“…This is particularly noticeable by the CNN antisymmetric stretching IR absorption of the nitrile imine moiety appearing over a wide range of frequencies (2000-2250 cm -1 ). [20,29,30] For instance, Bégué and Wentrup have theo-retically investigated different amino-, hydroxy-, and fluorosubstituted nitrile imines (R-CNN-H, H-CNN-R, and R-CNN-R; R = NH 2 , OH, and F) and predicted that some of the studied molecules should exhibit carbenic character. [17] In addition, theoretical studies have indicated that substituents bearing a lone-electron pair should increase the importance of the carbenic resonance structure of nitrile imines.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is particularly noticeable by the CNN antisymmetric stretching IR absorption of the nitrile imine moiety appearing over a wide range of frequencies (2000-2250 cm -1 ). [20,29,30] For instance, Bégué and Wentrup have theo-retically investigated different amino-, hydroxy-, and fluorosubstituted nitrile imines (R-CNN-H, H-CNN-R, and R-CNN-R; R = NH 2 , OH, and F) and predicted that some of the studied molecules should exhibit carbenic character. [17] In addition, theoretical studies have indicated that substituents bearing a lone-electron pair should increase the importance of the carbenic resonance structure of nitrile imines.…”
Section: Introductionmentioning
confidence: 99%
“…[17] In addition, theoretical studies have indicated that substituents bearing a lone-electron pair should increase the importance of the carbenic resonance structure of nitrile imines. [20,29,30] For instance, Bégué and Wentrup have theo-retically investigated different amino-, hydroxy-, and fluorosubstituted nitrile imines (R-CNN-H, H-CNN-R, and R-CNN-R; R = NH 2 , OH, and F) and predicted that some of the studied molecules should exhibit carbenic character. [30] These postulated carbenic nitrile imines were predicted to lack the intense IR absorption in the 2000-2250 cm -1 region that characterizes other nitrile imines.…”
Section: Introductionmentioning
confidence: 99%
“…Although some computational studies have already been undertaken on nitrile imines, [14] not much attention has been paid to the tetrazole activation step, [15] which in our opinion is crucial to understand their reactivity.H erein, density functional theory (DFT) calculationso ft he three tetrazoles, Tet, Py-Tet and Biph-Tet,w ere carriedo ut. First, an examination of the transitions of the ground state of the selected tetrazoles was carried out.…”
mentioning
confidence: 99%
“…In the case of a maximally depleted charge, it is possible to report which sites are able to stabilize an overload uptake of electronic charge and that they are especially reactive toward electron‐rich reactants (nucleophiles) . Additionally, studies dealing with chemical reactivity relationships and QTAIM have shown that the Laplacian can be reliably used to predict reactive sites, such as the positions of sites for electrophilic or nucleophilic attack in aromatic systems, N‐heterocyclic carbenes, α‐ and β‐halonaphthalenes, non‐steroidal anti‐inflammatory drugs, and other chemical systems …”
Section: Introductionmentioning
confidence: 99%
“…[3,4] Additionally, studies dealing with chemical reactivity relationships and QTAIM have shown that the Laplacian can be reliably used to predict reactive sites, such as the positions of sites for electrophilic or nucleophilic attack in aromatic systems, [5] N-heterocyclic carbenes, [6] αand β-halonaphthalenes, [7] non-steroidal anti-inflammatory drugs, [8] and other chemical systems. [9][10][11] Theoretical studies about reaction mechanisms are usually limited to the determination of the energetic paths that connect reactants, transition states, and products and their structures. In a previous work, we showed that the most important topological feature in the ethene protonation reaction over acidic zeolite is the electron charge density redistribution.…”
Section: Introductionmentioning
confidence: 99%